KEANEKARAGAMAN DAN HUBUNGAN KEKERABATAN ANTARA SPESIES ANGGOTA FAMILI ARACEAE BERDASARKAN MORFOLOGI DI DESA SIFAOROASI - Wantriyani Laia (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
Based on the background of this research problem, there are still many people who do not know that Araceae plants have many types of species which give rise to diversity and relationships between each other. This research aims 1) to find out the relationship between the Araceae family, 3) to find out the benefits of the Araceae family, 2) to find out the public's response to the Araceae family. The type of research used in this research is qualitative research. The place of this research is Sifaoroasi Village, Amandraya District, South Nias Regency. This research was carried out from May to June 2023. The data collection techniques for this research were interviews and documentation. This research data was analyzed using data reduction, verification and drawing conclusions. The conclusion from this research is that there are several types of araceae families found in Sifaoroasi Village, namely some food, medicinal and ornamental plants and there are 6 types of araceae plants found in Sifaoroasi Village, namely Alocasia, Colacasia, Homalomena, Coladium, Aglaonema, Schicmatoglottis. The suggestions offered by researchers are that it is hoped that this research can become a source of information about material diversity and kinship relationships between species belonging to the Araceae family based on morphological characters.